Controlling the Body: Power, 'Bare Life' and the Ownership of the Body in Select Contemporary Films - Sachin Rajeev (Singularities : A Transdisciplinary Biannual Research Journal, 2016)
Quantifying the 'humanness' of an entity has been the preoccupation of various societies since their inception. The act of quantification prompts us to ask: who or what a 'human' is? A 'human' was understood by many as anyone who belonged to the species Homo sapiens in the biological chain. The Italian philosopher Giorgio Agamben puts forth a different opinion on the issue in his work Homo Sacer. Agamben creates the categories of 'good life' and 'bare life'. 'Good life'adheres to the rules made by a sovereign power while 'bare life'has either transgressed those rules or is condemned since creation by the sovereign. The 'lives', 'livelihoods' and 'selves' of the latter are centred around rules made for them by powers greater than themselves. In effect, their 'humanness' is determined by these powers. The texts that I examine are three movies: Kazuo Ishiguro's Never Let Me Go(2010) directed by Mark Romaneck, Jodi Picolut'sMy Sister's Keeper (2009) by Nick Cassavetes and Repo Men(2010) by Alex Cox. The movies pose the central question of the ownership of the body which is a basic right in life. All the central characters are persecuted by various institutions (medical, economic or familial) which'own' them. They are ownedby either creating them with a purpose for existence (as clones for organ donation) or by remaking them with a luxury (like an artificial heart for instance) which they have to purchase. These movies make us question the very notion of humanity, what it is that defines/constitutes a human. When is a person fully in possession of himself (be it legally, biologically or economically).The factors used to confer the status of 'good life' and 'bare life' to people in the movies is utilitarian in nature. These questions blur the lines between the category ofHomo sapiens and theFoucauldian 'Homo Economicus'. I have made use of a biopolitic and posthumanist perspectivein myattempt to bring out the politics of self-propagationthrough the construction and discarding specific 'others' for the sustenance of the human race. Human nature is determined by different systems of power which work upon it. I look at the category of 'bare life' and how it is created by and conferred to 'humans' by the power structures they are subject to. I also seek to illustrate how the motives that drive these structures of controlare purely economic and utilitarian